Travelling-wave similarity solution for gravity-driven rivulet of a Newtonian fluid with strong surface-tension effect - Siti Sabariah, Abas; Yatim, Y.M (2017)
Rivulet flows occur in a wide range of practical situations ranging from industrial situation such as coating processes to geophysical situation such as lava flow, and extensive efforts have been made to investigate it. In this study, a lubrication approximation is used to investigate the gravity-driven draining of unsteady, slender, symmetric rivulet of Newtonian fluid down an inclined plane, with strong surface-tension effect. A travelling-wave similarity solution is obtained representing a quartic transverse profile rivulet and that it has a uniform thickness at any position x and time t which widen or narrow according to (x − ct)1/4, where c is a velocity of a rivulet and thicken or thin according to a free parameter F0.